Efficient bakers' yeast-catalyzed multicomponent synthesis of -aminophosphonates in one pot - Bhattacharya, Asish K.; Mujahid, Mohammad (Synthetic Communications, 2013)
Utilizing bakers' yeast (Saccharomyces cerevisiae) as a biocatalyst, synthesis of -aminophosphonates in one pot has been accomplished by the three-component reaction of an aldehyde, an amine, and diethyl phosphite in moderate to good yields under solvent-free reaction conditions. Supplemental materials are available for this article. Go to the publisher's online edition of Synthetic Communications (R) to view the free supplemental file.
Keywords: -aminophosphonates; aldehydes; amines; green chemistry; Saccharomyces cerevisiae; solvent-free conditions